ID: 22. Issue 4 (April 2016) - Majumdar, S; Rinaldi, JC; Gauntner, T; Xie, L; Hu, W; Prins, GS; Malhotra, N; Kasper, S
Abstract : Genomic signaling via estrogen receptors (ER) has been widely studied and implicated as the main ER signaling pathway in prostate development and carcinogenesis. Non-genomic ER signaling has also been reported in prostate epithelium although down-stream cascades have not been clarified. Our lab has recently identified ERs in human prostate epithelial stem/progenitor cells and shown that that 17β-estradiol (E2) can stimulate stem cell symmetric self-renewal and progenitor cell proliferation. In this study we interrogate non-genomic membrane initiated ER signaling in this prostate stem/progenitor cell population. Human prostate stem-progenitor cells were enriched from primary prostate epithelial cell cultures (PrEC) of young, disease-free donors using a 3D prostasphere (PS) model as previously described. Cells were labeled using ERα or ERβ antibodies along with prostate stem cell markers CD49f and TROP2 followed by triple channel FACS to quantify ERα + /ERβ + cell numbers. To explore ERα, the benign human prostate stem cell line WPE with extremely low levels of ERα and ERβ, was stably transfected with a lentiviral-ERα expression vector. The human prostate cancer stem-like cell line HuSLC (ERβ ++, ERα − ) was utilized to interrogate ERb actions. Cells were exposed to 10 nM estradiol (E2) over a 15 to 60 minute time course +/− ICI 182, 870 (ICI), an ERα/β antagonist. FACS analysis of day 7 PS cells labeled for ERα or ERβ revealed 66% of day 7 PS cells as ERα + and 40% as ERβ + . Among ERα or ERβ positive PS cells, 4% were Trop2 + /CD49f high (stem-like cells) and 10–12% were Trop2 + /CD49f medium (early stage progenitor cells). PS exposed to 10 nM E2 showed sequential phosphorylation of Src, Erk1/2, p38, Akt and NFκB (p65) over 60 minutes. Phosphorylation of up-and downstream targets (EGFR, Jnk, GSK 3α/β, p70 S6 kinase, PRAS40, MSK1/2) was also seen using a phospho-kinase array. Furthermore, phosphorylation of ERα at S167 was noted over 60 min of E2 exposure enabling enhancement of genomic ERα transactivational activity in a feed-forward manner. ICI attenuated Akt and Erk1/2 phosphorylation, confirming membrane bound ERs are involved in downstream signaling. E2 treatment of HuSLCs showed phosphorylation of Erk1/2 but not Akt, indicating that ERβ signals exclusively through the MAPK pathway in these cells. Conversely, E2 treatment of WPE-stem cells overexpressing ERα resulted in robust phosphorylation of Akt but lower levels of Erk1/2 phosphorylation suggesting that Akt activation may be more reliant on ERα signaling. To identify pathway specific roles, specific inhibitors were added to PS cultures. PS treated with LY294002 (Akt inhibitor) for 7 days attenuated the E2-mediated increase in PS number and size. Inhibition of the NFκB downstream of the Akt pathway by IKK VII (IKK inhibitor) blocked p65 phosphorylation, abrogated the E2-induced increase in stem cell symmetric self-renewal and blunted E2 stimulation of progenitor cell proliferation. Analysis of PS cyclin mRNA levels revealed a G1 arrest of progenitor cells upon IKK inhibition suggesting an essential role of NFκB in progenitor cell amplification. MAPK pathway inhibition with U0126(Erk1/2 inhibitor) resulted in an attenuation of the E2-mediated increase in PS number and size and an increase stem cell symmetric self-renewal suggesting that MAPK pathway activation promotes commitment to stem and progenitor cell expansion. Taken together, the present findings reveal that human prostate stem-progenitor cells express both ERα and ERβ which differentially activate different signaling cascades originating at the membrane. These signaling events may lead to unique downstream actions that influence prostate stem-progenitor cell proliferation as well as lineage commitment decisions.